Kebijakan Pemerintah dalam Penanganan Pencemaran Minyak di Perairan Laut - Intan Fandini; Suwari Akhmaddhian (Universitas Kuningan, 2022)
Marine pollution is the entry/inclusion of living things, energy substances and or other components into the marine environment by human activities so that the quality decreases to a certain level which causes the marine environment to no longer comply with quality standards and/or functions. One of the cases related to environmental pollution that caused damage to the marine environment was the Oil Spill in the Back Sea Waters of Padang, Batam, Riau Islands Province. The purpose of this paper is to find out how the policy in the petroleum sector in Indonesia is, how is the regulation of Indonesian national law to prevent, reduce and control the problem of marine pollution by oil, how is the impact of oil spills in sea waters from oil and gas industry activities on the environment. The method used in this research is the normative juridical method. Using qualitative analysis with the resulting data in the form of secondary data obtained from previous research, laws and regulations and other sources. The result of this research is that the policy of the petroleum sector in Indonesia to achieve energy security is pursued by applying the concept of State Controlling Rights (HMN). The philosophy of